Urban Farming sebagai Solusi Ekonomis dimasa Pendemi Covid-19 (di Kelurahan Gilingan , Kecamatan Banjarsari, Surakarta) - Siti Hayati Efi Friantin; Ika Swasti Putri (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
During the Covid-19 pandemic, many are at home, many businesses are out of business. Everyone has experienced the impact of the Covid-19 pandemic. The country's economy has declined drastically, moreover the family economy has become uncertain and the body of the group has a low standard of living. The family income is getting smaller while the family expenses still have to be paid. Each family must think hard to survive in the uncertainty of the end of the Covid-19 pandemic. Therefore, saving costs for the family must start from self-initiative and if necessary this idea is transmitted to other communities. One of the economical solutions / family cost savings is Urban Farming. Urban Farming is urban farming by utilizing narrow land or around the yard of the house. The purpose of this activity is to save/economize family expenditures as well as urban farming training which is often called Urban Farming. As a result of this service, participants can apply Urban Farming in their surrounding environment to improve the family's economy The Cinderejo Kidul area, Gilingan Village, Banjarsari District was chosen as the location for this service activity because it is located not far from STIE AUB and has also been carried out regularly and continuously.